PERAN INTEGRATIF AGAMA-AGAMA DALAM MENGATASI MASALAH KEMISKINAN DI BANJARASRI KALIBAWANG KULONPROGO DAERAH ISTIMEWA YOGYAKARTA DENGAN PENDEKATAN SOSIOLOGI DAN PSIKOLOGI - Dian Nur Anna (Religi: Jurnal Studi Agama-agama, 2014)
This study aims to determine the poverty problems of Banjarasri society in Kalibawang, Kulonprogro, the Special Territory of  Yogyakarta in sociolog y and psychological perspective. The study tries to map out the main problems of the poverty and to look for alternatives solution of  the problem. Implementing grounded research and integrative review on the role of  religions in society, the study proves that religions are even able to help in solving the problem of poverty. The study then concluded that religious institutions have important roles in overcoming poverty problem through various economic, social and educational programs.